Role of Genetic Variants AGT rs699 and ACE2 rs2106809 in Increasing the Risk and Severity of COVID-19 Infection in Iraqi Patients - Hussein, Ghazwan Faisal; Al Saadi, Ali Hmood (Iraqi Journal of Science, 2024)
The main aim of our study was to determine if the ACE2 rs2106809 and AGT rs699 polymorphisms increase the risk and severity of Covid-19 infection in Iraqi patients. This case-control study included 102 patients (mean age 52.66±18.82 years) and 92 healthy (mean age 37.88±14.19 years). The patients were grouped based on severity: hospitalized (n = 57) and non-hospitalized (n = 45). Demographic and comorbidity data was also collected. Genotype distribution of two selected SNPs ACE2 gene rs2106809 and AGT rs699 polymorphisms was performed by allele-specific PCR (AS-PCR) and sanger sequencing. The ACE2 rs2106809 C allele was associated to an increased risk of Covid-19 infection and the severity in males but not in the females (C vs. T OR = 3.04 p=0.01 and C vs. T OR = 4.9, p = 0.03, respectively). While AGT rs699 TC genotype was associated with 2.96 folds higher risk of Covid-19 infection (TC vs.TT, CC OR =2.96, 95%CI = 1.12–6.44; p = 0.02). The AGT rs699 was not associated with the severity of infection. Among outpatients, benign conditions were associated with a lower risk, however older age males and comorbidities increased the risk. We concluded that the genetic variant of rs2106809 ACE2 in males was significant with a risk of infection and severe clinical course because it could be located on the X-chromosome, and at the same time AGT rs699 polymorphism had an impact on the increased risk of Covid-19 but had no relation with the severity of Covid-19.